Fe3mo3n / mo2c dual-phase carbon-based composite electromagnetic shielding material and preparation method and application thereof
Patent Information
- Application Number
- CN202611194663.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-11-03
AI Technical Summary
When existing electromagnetic shielding materials increase the content of magnetic components to enhance magnetization, it is easy to cause an imbalance between the complex dielectric and magnetic parameters of the material, resulting in poor impedance matching, excessive reflection contribution, and affecting the shielding effect. Furthermore, it is difficult to achieve synergistic optimization of dielectric loss and magnetic loss in a simple fabrication process.
By adjusting the ratio of iron to molybdenum, the composition of Fe3Mo3N and Mo2C crystal phases was controlled, and a Fe3Mo3N/Mo2C dual-phase carbon-based composite electromagnetic shielding material was prepared. The dielectric loss and magnetic loss were synergistically optimized by utilizing the heterogeneous interface at the nanoscale. The preparation method employed ethanol-assisted grinding and heat treatment under a nitrogen atmosphere.
An electromagnetic shielding material with high shielding effectiveness and high effective absorption coefficient has been developed, with an average total shielding effectiveness of 7.55dB, a maximum total shielding effectiveness of 11.27dB, and an average effective absorption coefficient as high as 71.7%, solving the problem of excessive reflection from traditional materials.
Smart Images

Figure CN123035658A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of electromagnetic shielding materials technology, specifically, it relates to a Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material, its preparation method and application. Background Technology
[0002] With the widespread application of electronic devices, miniaturized communication systems, and high-frequency circuits, the resulting electromagnetic interference can not only affect the normal operation of electronic devices but also pose a threat to information security. Therefore, developing high-performance electromagnetic shielding materials is of great significance for ensuring equipment reliability and environmental adaptability. Electromagnetic shielding materials typically attenuate incident electromagnetic waves through reflection, absorption, and multiple reflections. While traditional metallic materials possess high electrical conductivity, they have limitations in terms of density, corrosion resistance, processability, and impedance matching.
[0003] Transition metal carbides, transition metal nitrides, and their carbon-based composites possess tunable conductivity, magnetic response, and interface structure, making them promising candidate systems for electromagnetic shielding materials. Simply increasing the content of magnetic components to enhance magnetization often leads to an imbalance between the material's complex dielectric and magnetic parameters, resulting in poor impedance matching and a reduced effective absorption ratio of electromagnetic waves. It may even negatively impact shielding effectiveness due to excessive reflection contributions. Furthermore, achieving synergistic optimization of dielectric and magnetic losses in a simple fabrication process while avoiding the formation of impurity phases remains a significant challenge for current technologies.
[0004] Therefore, there is an urgent need for a carbon-based composite shielding material with a simple preparation process and controllable phase, which can balance dielectric and magnetic losses through component regulation and solve the impedance mismatch problem associated with magnetic enhancement. Summary of the Invention
[0005] The purpose of this application is to provide a Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material, its preparation method and application. By adjusting the ratio of iron and molybdenum in the raw materials, the composition of Fe3Mo3N and Mo2C crystal phases in the product can be precisely controlled, thereby achieving synergistic optimization of dielectric loss and magnetic loss, and thus preparing an electromagnetic shielding material with high shielding effectiveness and high effective absorption coefficient.
[0006] To achieve the above objectives, this application provides a Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material. The composite electromagnetic shielding material includes a carbon matrix and Fe3Mo3N and Mo2C crystalline phases dispersed in the carbon matrix. The Fe3Mo3N and Mo2C crystalline phases are in contact with each other at the nanoscale to form a heterogeneous interface.
[0007] Furthermore, the mass fraction of carbon in the composite electromagnetic shielding material is 27%~30%, and the mass fraction of nitrogen is 3.0%~5.5%.
[0008] Furthermore, the high-field magnetization of the composite electromagnetic shielding material under a magnetic field of 298K and 10kOe is 5 emu·g. -1 ~20emu·g -1 Its coercivity is 80 Oe to 200 Oe.
[0009] On the other hand, this application also provides a method for preparing Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material, comprising the following steps: Iron salt, molybdenum salt and melamine were used as precursors. They were ground and mixed evenly with the aid of ethanol, and then dried to obtain powdered precursors. The powdered precursor was heated to 680℃~720℃ in a nitrogen atmosphere and held at that temperature. After cooling, Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material was obtained.
[0010] Furthermore, the iron salt is a soluble divalent iron salt or a soluble trivalent iron salt, including at least one of ferrous sulfate heptahydrate, ferric chloride hexahydrate, and ferric nitrate nonahydrate; the molybdenum salt is a molybdenum-containing ammonium salt, including ammonium molybdate or ammonium heptamolybdate tetrahydrate; the molar ratio of molybdenum salt to melamine is 1:20.
[0011] Furthermore, in the precursor, the amount of iron accounts for 25% to 50% of the total amount of iron and molybdenum.
[0012] Furthermore, in the precursor, the amount of iron accounts for 25% of the total amount of iron and molybdenum, and the molar ratio of ferric nitrate nonahydrate, ammonium heptamolybdate tetrahydrate, and melamine is 7 / 3:1:20.
[0013] Furthermore, the powdered precursor is heated to 680℃~720℃ under a nitrogen atmosphere and held at that temperature, including: purging with nitrogen at a flow rate of 450sccm~550sccm for 8min~12min before heating; adjusting the nitrogen flow rate to 95sccm~105sccm, heating to 680℃~720℃ at a rate of 3℃ / min~7℃ / min, and holding at that temperature for 100min~150min.
[0014] Further cooling methods include: continuously introducing nitrogen gas and cooling the furnace to room temperature.
[0015] On the other hand, this application also provides an application of Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material, that is, using Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material as a functional filler to prepare electromagnetic interference shielding components or electromagnetic wave attenuation components.
[0016] In summary, this application has the following beneficial effects: 1. This application uses common iron salts, molybdenum salts and melamine as raw materials, and the target product can be obtained by ethanol-assisted grinding and one heat treatment. It does not require complicated equipment or expensive precious metal catalysts, the preparation process is short and suitable for large-scale production.
[0017] 2. This application effectively controls the ratio of Fe3Mo3N and Mo2C dual phases in the product by precisely controlling the Fe / Mo feeding ratio in the precursor. Subsequent experiments show that when the Fe element feeding ratio is controlled at 25%~50%, the formation of iron carbide impurity phase can be avoided, ensuring the purity and structural stability of the material.
[0018] 3. The composite electromagnetic shielding material prepared in this application utilizes the Fe3Mo3N crystal phase to introduce magnetic loss, and the Mo2C crystal phase and carbon matrix to provide dielectric loss. Furthermore, it enhances interfacial polarization and multiple scattering through nanoscale heterogeneous interfaces. In particular, the material exhibits optimal impedance matching characteristics when the Fe element content is 25%. Under test conditions of 30wt% filler and approximately 2.0mm thickness, its average total shielding effectiveness reaches 7.55dB in the 1GHz~18GHz range, with a maximum total shielding effectiveness of 11.27dB, and an average effective absorption coefficient as high as 71.7%, demonstrating excellent absorption-type shielding characteristics and effectively solving the problem of excessive reflection in traditional high-magnetic materials.
[0019] 4. Characterization by SEM and TEM revealed that the composite electromagnetic shielding material prepared in this application possesses a porous cluster structure formed by stacked nanoparticles, with Fe3Mo3N in close contact with the Mo2C crystalline phase. This hierarchical structure not only increases the propagation path of electromagnetic waves but also provides abundant heterogeneous interfaces, which is beneficial for electromagnetic wave attenuation. Attached Figure Description
[0020] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the description of the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 These are the XRD patterns and standard card peak positions of samples with different Fe ratios proposed in the embodiments of this application.
[0022] Figure 2 These are the total shielding effectiveness (SET) curves of different samples in the range of 1 GHz to 18 GHz proposed in the embodiments of this application.
[0023] Figure 3 These are the VSM hysteresis loops of samples with different Fe ratios proposed in the embodiments of this application.
[0024] Figure 4 These are curves of the real part ε′, imaginary part ε″, real part μ′, and imaginary part μ″ of the complex permittivity for samples with different Fe ratios proposed in the embodiments of this application.
[0025] Figure 5 These are SEM images of the GC-25 sample proposed in the embodiments of this application, wherein, Figure 5 In the figure, A and B represent the surface morphology at 40,000 times magnification (scale bar of 200 nm) and 20,000 times magnification (scale bar of 500 nm), respectively.
[0026] Figure 6 These are TEM and HRTEM images of the GC-25 sample proposed in the embodiments of this application; wherein, Figure 6 The AC values in the images are TEM images at 200nm, 100nm, and 50nm, respectively. Figure 6 In the figure, D represents the HRTEM image and the lattice fringes. Detailed Implementation
[0027] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0028] The widespread application of various portable electronic terminals, micro-communication devices, and high-frequency integrated circuits has led to a continuous increase in the density of electromagnetic radiation signals in the working environment. Electromagnetic coupling interference between devices is frequent, and external stray electromagnetic waves can easily cause circuit signal distortion and component operating state deviations. Furthermore, electromagnetic signals radiated outwards by the devices themselves can lead to information leakage and electromagnetic pollution. Therefore, electromagnetic shielding materials have become a key supporting functional material for ensuring the stable operation of electronic systems. Existing electromagnetic shielding materials attenuate incident electromagnetic waves mainly through three pathways: surface reflection, internal absorption, and interlayer multiple reflections. Different material systems rely on their inherent electrical and magnetic properties to form differentiated electromagnetic wave loss mechanisms. For example, traditional metallic shielding materials have excellent free electron conductivity, achieving considerable shielding effects. However, their high density makes them prone to oxidation and corrosion during long-term use, and they are difficult to mold and composite process. Simultaneously, the significant impedance difference between metal and air means that most incident electromagnetic waves are directly reflected from the material surface, resulting in a low absorption loss ratio. The reflected electromagnetic waves can cause secondary interference inside the device, making it difficult to meet the protection requirements of lightweight devices with low reflection loss.
[0029] Transition metal carbide and nitride carbon-based composite materials exhibit tunable electrical conductivity, magnetic response behavior, and microstructure, making them a key research area for novel electromagnetic shielding materials. The shielding effectiveness of these materials is determined by the synergistic effect of dielectric and magnetic losses. Simply increasing the content of the magnetic component within the system, while enhancing magnetization and magnetic loss, alters the material's complex dielectric parameters, leading to increased interface reflection and a reduced effective absorption ratio. Current processes struggle to simultaneously generate both Fe3Mo3N and Mo2C functional crystalline phases in a single heat treatment process, making it impossible to construct sufficient heterogeneous interfaces using two-phase nano-symbiotic structures to promote interface polarization and electromagnetic wave scattering.
[0030] Based on this, in a first aspect, this application provides a Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material, comprising a carbon matrix and Fe3Mo3N and Mo2C crystalline phases dispersed in the carbon matrix, wherein the Fe3Mo3N and Mo2C crystalline phases are in contact with each other at the nanoscale to form a heterogeneous interface.
[0031] In the Fe3Mo3N / Mo2C biphase carbon-based composite electromagnetic shielding material of this application, the close nano-contact between the two phases constructs a large number of nano-heterogeneous interfaces. The different phases exhibit differences in conductivity and permeability, leading to interfacial polarization and space charge polarization at the interfaces when electromagnetic waves are incident, thus introducing additional dielectric loss. Simultaneously, the heterogeneous interfaces alter the electromagnetic wave propagation path, inducing multiple scattering and extending the propagation distance of electromagnetic waves within the material, effectively converting electromagnetic energy into heat energy loss. This application achieves synergistic enhancement of dielectric and magnetic losses by simultaneously introducing the magnetic loss of nitrides and the conductive dielectric loss of carbides, overcoming the shortcomings of single Mo2C having no magnetic loss and single iron-based materials having poor dielectric matching.
[0032] In this application, when X-ray diffraction tests were performed using Cu Kα radiation within a 2θ range of 10° to 80°, the X-ray diffraction pattern of the composite electromagnetic shielding material simultaneously exhibited characteristic diffraction peaks attributable to both the Fe3Mo3N and Mo2C crystal phases, but no characteristic diffraction peaks clearly attributable to the iron carbide crystal phase were detected. This indicates that the preparation method of this application can simultaneously generate two types of functional loss phases in situ in one step. The two loss components coexist uniformly in the carbon matrix, rather than being a simple physical mixture, and the interface between the two phases is stable, enabling stable dielectric-magnetic synergistic loss. Furthermore, the relative content of the two phases can be precisely controlled by adjusting the Fe / Mo feed ratio to flexibly match electromagnetic waves of different frequency bands.
[0033] As some optional embodiments of this application, the carbon content in the composite electromagnetic shielding material is 27%~30% by mass, and the nitrogen content is 3.0%~5.5% by mass. Since the carbon matrix itself has good conductivity, a carbon content of 27wt%~30wt% can form a continuous conductive path within the material. Electron migration leads to conductivity loss, providing a basic source of dielectric loss for electromagnetic wave attenuation. If the carbon content is below 27%, the conductive network breaks down, potentially reducing conductivity loss; if the carbon content is above 30%, the dielectric constant of the material will increase significantly, widening the difference with air impedance, causing a surge in electromagnetic wave surface reflection, which will actually reduce the effective absorption ratio. Furthermore, an appropriate amount of carbon matrix acts as a carrier, uniformly isolating Fe3Mo3N and Fe3Mo3N nanocrystals, preventing grain agglomeration and ensuring full exposure of the two-phase nano-heterogeneous interface, thus maximizing interfacial polarization loss. Moreover, the carbon framework simultaneously forms a multi-level porous structure, which can extend the electromagnetic wave transmission path and enhance scattering loss.
[0034] As one of the optional embodiments of this application, the high-field magnetization of the composite electromagnetic shielding material under a magnetic field of 298K and 10kOe is 5 emu·g. -1 ~20emu·g -1The coercivity is 80 Oe to 200 Oe. The composite electromagnetic shielding material is dispersed in paraffin at a mass fraction of 30 wt% and made into a ring-shaped test body with a thickness of 1.98 mm to 2.02 mm. When tested using the coaxial transmission line method in the range of 1 GHz to 18 GHz, the average total shielding effectiveness of the ring-shaped test body is not less than 7.3 dB, the maximum total shielding effectiveness is not less than 10.5 dB, and the average effective absorption coefficient is not less than 70%.
[0035] Secondly, based on a general inventive concept, this application also provides a method for preparing the above-mentioned Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material, including the following steps: S1. Using iron salt, molybdenum salt and melamine as precursors, the mixture is ground and mixed evenly with the aid of ethanol, and then dried to obtain a powdered precursor.
[0036] As some optional embodiments of this application, the iron salt is a soluble divalent iron salt or a soluble trivalent iron salt, including at least one of ferrous sulfate heptahydrate, ferric chloride hexahydrate, and ferric nitrate nonahydrate (Fe(NO3)3·9H2O); the molybdenum salt is a molybdenum-containing ammonium salt, including ammonium molybdate or ammonium heptamolybdate tetrahydrate ((NH4)6Mo7O). 24 (·4H2O); the molar ratio of molybdenum salt to melamine is 1:20. Melamine is used to provide carbon and nitrogen sources and is beneficial for the formation of carbon-based composite structures.
[0037] As some optional embodiments of this application, the amount of iron in the precursor accounts for 25% to 50% of the total amount of iron and molybdenum. Preferably, the amount of iron in the precursor accounts for 25% of the total amount of iron and molybdenum, and the molar ratio of ferric nitrate nonahydrate, ammonium heptamolybdate tetrahydrate, and melamine is 7 / 3:1:20.
[0038] In this application, the Fe molar percentage is calculated as n(Fe) / [n(Fe)+n(Mo)]×100%, where n(Fe) and n(Mo) are the amounts of Fe and Mo elements in the precursor, respectively. A concentration of 25% to 50% is beneficial for obtaining a Fe3Mo3N / Mo2C dual-phase composition and suppressing significant iron carbide impurities, with 25% being more preferred.
[0039] S2. The powdered precursor was heated to 680℃~720℃ under a nitrogen atmosphere and kept at that temperature. After cooling, Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material was obtained.
[0040] As some optional embodiments of this application, the powdered precursor is heated to 680℃~720℃ in a nitrogen atmosphere and held at that temperature. This includes: purging with nitrogen at a flow rate of 450sccm~550sccm for 8min~12min before heating; adjusting the nitrogen flow rate to 95sccm~105sccm, heating to 680℃~720℃ at a rate of 3℃ / min~7℃ / min, and holding at that temperature for 100min~150min. If the residual air in the tubular furnace contains oxygen, it will oxidize the Fe and Mo precursors at high temperatures, generating metal oxide impurities, consuming carbon and nitrogen sources, and destroying the formation environment of Fe3Mo3N and Mo2C. Therefore, this application uses high-flow-rate, high-speed nitrogen to quickly replace the air in the furnace, making the reaction atmosphere an oxygen-free, inert atmosphere, thus eliminating the formation of oxidized impurity phases at the source. After purging, reducing the nitrogen flow rate can maintain an inert protective atmosphere and prevent the high-speed flow from carrying away the gaseous nitrogen and carbon active intermediates. At the same time, the stable flow rate ensures that the nitrogen partial pressure in the furnace is constant, providing a stable reaction atmosphere for the Fe3Mo3N nitriding and Fe3Mo3N carbonization reactions, and ensuring the simultaneous formation of the two phases.
[0041] As some optional embodiments of this application, the cooling method includes: continuously introducing nitrogen gas and cooling the furnace to room temperature. At high temperatures, the crystalline structure is unstable. If exposed to air for rapid cooling, the high-temperature nanocrystals are easily oxidized upon contact with oxygen. Therefore, this application continuously introduces nitrogen gas and slowly cools the furnace after the reaction, stabilizing and solidifying the two-phase crystalline structure, preserving the complete nano-heterogeneous interface and pore structure, and avoiding oxidation failure.
[0042] Thirdly, based on a general inventive concept, this application also provides applications of the aforementioned Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material, including: using the Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material as a functional filler to prepare electromagnetic interference shielding components or electromagnetic wave attenuation components. It can be further processed into pressed sheets, coatings, polymer-based composite sheets, or other electromagnetic functional components. In specific embodiments, the shielding effectiveness of the component can be adjusted according to the matrix type, material filling ratio, component thickness, compaction density, and target frequency band, and should be tested for specific components.
[0043] The technical solutions described above in this application will be explained in detail below with reference to specific embodiments.
[0044] The Fe molar percentage in this application is calculated according to the following formula: Fe molar percentage = n(Fe) / [n(Fe) + n(Mo)] × 100%. Wherein, n(Fe) is the amount of Fe provided by the iron salt, and n(Mo) is the amount of Mo provided by the molybdenum salt. Samples with Fe molar percentages of 0%, 25%, 50%, and 75% are designated as GC-0, GC-25, GC-50, and GC-75, respectively. Unless otherwise specified, all sample names in this specification use the above codes.
[0045] Example 1 This embodiment provides a Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material, which is prepared by the following method: (1) Weigh 0.618g (0.0005mol) ammonium heptamolybdate tetrahydrate, 0.417g (0.0012mol) ferric nitrate nonahydrate and 1.261g (0.01mol) melamine as raw materials, mix them in a mortar, add ethanol and perform wet grinding to form a precursor slurry; (2) The precursor slurry is dried to remove ethanol until constant weight is achieved, and then ground into powder to obtain powdered precursor. (3) The powdered precursor was loaded into a quartz boat and placed together in the constant temperature zone of a tube furnace. Before heating, nitrogen gas was introduced at a flow rate of 500 sccm for 10 min to purge the air in the furnace. (4) Adjust the nitrogen flow rate to 100 sccm and continue to introduce nitrogen, then raise the temperature to 700℃ at a rate of 5℃ / min and keep it at that temperature for 2 hours; (5) After the heat preservation is completed, stop heating, keep nitrogen gas flowing in, and cool the furnace to room temperature to obtain Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material, named GC-25 sample (the molar percentage of iron is 25%).
[0046] Example 2 This embodiment provides a Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material, which is prepared by the following method: (1) Weigh 0.618g (0.0005mol) ammonium heptamolybdate tetrahydrate, 1.414g (0.0035mol) ferric nitrate nonahydrate and 1.261g (0.01mol) melamine as raw materials, mix them in a mortar, add ethanol and perform wet grinding to form a precursor slurry; (2) The precursor slurry is dried to remove ethanol until constant weight is achieved, and then ground into powder to obtain powdered precursor. (3) The powdered precursor was loaded into a quartz boat and placed together in the constant temperature zone of a tube furnace. Before heating, nitrogen gas was introduced at a flow rate of 500 sccm for 10 min to purge the air in the furnace. (4) Adjust the nitrogen flow rate to 100 sccm and continue to introduce nitrogen, then raise the temperature to 700℃ at a rate of 5℃ / min and keep it at that temperature for 2 hours; (5) After the heat preservation is completed, stop heating, keep nitrogen gas flowing in, and cool the furnace to room temperature to obtain Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material, named GC-50 sample (the molar percentage of iron is 50%).
[0047] Example 3 This embodiment provides a Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material, which is prepared by the following method: (1) Weigh 0.618g (0.0005mol) ammonium heptamolybdate tetrahydrate, 4.242g (0.0105mol) ferric nitrate nonahydrate and 1.261g (0.01mol) melamine as raw materials, mix them in a mortar, add ethanol and perform wet grinding to form a precursor slurry; (2) The precursor slurry is dried to remove ethanol until constant weight is achieved, and then ground into powder to obtain powdered precursor. (3) The powdered precursor was loaded into a quartz boat and placed together in the constant temperature zone of a tube furnace. Before heating, nitrogen gas was introduced at a flow rate of 500 sccm for 10 min to purge the air in the furnace. (4) Adjust the nitrogen flow rate to 100 sccm and continue to introduce nitrogen, then raise the temperature to 700℃ at a rate of 5℃ / min and keep it at that temperature for 2 hours; (5) After the heat preservation is completed, stop heating, keep nitrogen gas flowing in, and cool the furnace to room temperature to obtain Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material, named GC-75 sample (the molar percentage of iron is 75%).
[0048] Comparative Example 1 This comparative example provides an electromagnetic shielding material, which is prepared by the following method: This embodiment provides a Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material, which is prepared by the following method: (1) Weigh 0.618g (0.0005mol) ammonium heptamolybdate tetrahydrate and 1.261g (0.01mol) melamine as raw materials, mix them in a mortar, add ethanol and perform wet grinding to form a precursor slurry; (2) The precursor slurry is dried to remove ethanol until constant weight is achieved, and then ground into powder to obtain powdered precursor. (3) The powdered precursor was loaded into a quartz boat and placed together in the constant temperature zone of a tube furnace. Before heating, nitrogen gas was introduced at a flow rate of 500 sccm for 10 min to purge the air in the furnace. (4) Adjust the nitrogen flow rate to 100 sccm and continue to introduce nitrogen, then raise the temperature to 700℃ at a rate of 5℃ / min and keep it at that temperature for 2 hours; (5) After the heat preservation is completed, stop heating, keep nitrogen gas flowing in, and cool the furnace to room temperature to obtain Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material, named GC-0 sample (the molar percentage of iron is 0%).
[0049] Experimental Example The samples from Examples 1-3 and Comparative Example 1 were mixed with paraffin wax to prepare ring-shaped test bodies that matched the coaxial test fixture. The mass fraction of the sample to be tested in the ring-shaped test body was 30%, and the mass fraction of paraffin wax was 70%. The phase composition of the materials was determined by X-ray diffraction; the overall carbon, nitrogen, hydrogen, and sulfur content of the materials was determined by elemental analysis; the magnetism was evaluated using hysteresis loops obtained from a vibrating sample magnetometer; and the electromagnetic shielding performance was calculated using scattering parameters measured by a vector network analyzer. For the ring-shaped test bodies matched with the coaxial test fixture, complex scattering parameters were measured in the range of 1 GHz to 18 GHz using an Agilent E5071C vector network analyzer, and the complex permittivity, complex permeability, and corresponding electromagnetic shielding parameters were further obtained.
[0050] Specifically, it includes: 1. XRD phase analysis X-ray diffraction tests were performed on GC-0, GC-25, GC-50, and GC-75 samples using Cu Kα radiation, with a scanning range of 2θ = 10° to 80°. The obtained XRD patterns are shown below. Figure 1 As shown in the figure. The obtained experimental spectra were compared with the Mo2C standard card PDF#77-0720 and the Fe3Mo3N standard card PDF#48-1408, respectively. The parameters of the obtained sample phases and the toroidal test body are shown in Table 1.
[0051] Table 1. Parameters of sample phase and test body
[0052] As shown in Table 1, the main diffraction peaks of sample GC-0 can be attributed to Mo2C. Sample GC-25 exhibits characteristic diffraction peaks attributable to both Mo2C and Fe3Mo3N, and no characteristic diffraction peaks clearly attributable to iron carbide were detected under the current testing conditions. The Fe3Mo3N-related diffraction characteristics in sample GC-50 are further enhanced. The diffraction peak composition of sample GC-75 is more complex, and additional diffraction signals attributable to iron carbide are observed.
[0053] The above results indicate that the crystal phase composition of the product can be changed by adjusting the Fe / Mo feeding ratio.
[0054] 2. Magnetic Characterization of VSM The hysteresis loops of four groups of samples were tested at approximately 298 K under an applied magnetic field ranging from -10 kOe to 10 kOe. Considering that some samples did not exhibit complete magnetic saturation at 10 kOe, the magnetization at 10 kOe was used as the high-field magnetization M. 10 kOe, instead of expressing it as saturation magnetization. The test results are shown in Table 2 and Figure 3 As shown.
[0055] Table 2 Statistical Results of VSM Measurement
[0056] As shown in Table 2, with the increase of Fe molar percentage, the high-field magnetization of the sample decreased from 0.815 emu·g. -1 Increased to 22.239 emu·g -1 The coercivity increased from 17.0 Oe to 241.6 Oe, indicating that the overall magnetic response of the material can be effectively adjusted by changing the Fe / Mo feeding ratio.
[0057] 3. Electromagnetic shielding performance test Using an Agilent E5071C vector network analyzer and a coaxial transmission line test fixture, after completing two-port calibration, the complex scattering parameters S of each ring test specimen were measured in the range of 1 GHz to 18 GHz. 11 and S 21 Each curve includes 1601 frequency points, and the test results are shown in Table 3 and... Figure 2 As shown.
[0058] Calculate the reflection coefficient R, transmission coefficient T, and absorption coefficient A based on the scattering parameters: R = |S 11 | 2 T=|S 21 | 2 A=1 R T.
[0059] Total shielding effectiveness SET, reflective shielding effectiveness SER, absorptive shielding effectiveness SEA, and effective absorption coefficient Aeff are calculated according to the following formula: Total shielding effectiveness SET = 10log 10 T, Reflection shielding effectiveness SER= 10log 10 (1 R), absorption and shielding effectiveness SEA= 10log 10 [T / (1 R)], effective absorption coefficient Aeff=A / (1 R).
[0060] Table 3 Electromagnetic shielding parameters of the ring-shaped test object in the range of 1 GHz to 18 GHz
[0061] As shown in Table 3, the SET of the GC-25 sample is no less than 6 dB in the 5.12 GHz to 18 GHz range, no less than 8 dB in the 8.75 GHz to 18 GHz range, and no less than 10 dB in the 14.86 GHz to 17.17 GHz range. The average SET, maximum SET, and average Aeff of GC-25 are the highest among the four sample groups. It should be noted that the average Aeff in this application is the effective absorption ratio after deducting surface reflections, and is not equivalent to the absolute absorption rate relative to all incident electromagnetic waves.
[0062] 4. Analysis of complex dielectric and complex magnetic parameters Based on the complex scattering parameters measured by the Agilent E5071C vector network analyzer, the complex permittivity and complex permeability of four test specimens in the range of 1 GHz to 18 GHz were obtained using the instrument's material parameter inversion method. The complex permittivity is expressed as ε. =ε′ jε″, the complex permeability is expressed as μ =μ′ jμ″. The dielectric loss tangent and magnetic loss tangent were calculated using tanδε=ε″ / ε′ and tanδμ=μ″ / μ′ respectively, and the test results are as follows: Figure 4 As shown in the figure. Accordingly, Table 4 lists the average values of each parameter in the corresponding frequency band.
[0063] Table 4. Average values of complex permittivity / complex magnetism parameters in the 1GHz~18GHz range
[0064] As shown in Table 4, sample GC-25 has the highest average dielectric loss tangent among the four groups, and its average magnetic loss tangent is significantly higher than that of GC-0. Although GC-50 and GC-75 have higher average μ′ and higher high-field magnetization, their average SET and average Aeff did not continue to increase. These results indicate that under the test conditions, the shielding effectiveness does not change monotonically with either the dielectric constant or the magnetic response alone, but is jointly related to dielectric loss, magnetic loss, and their matching state.
[0065] 5. Elemental composition analysis The mass fractions of carbon, nitrogen, hydrogen, and sulfur in samples GC-0, GC-25, GC-50, and GC-75 were determined using a CHNS elemental analyzer. The test results are shown in Table 5.
[0066] Table 5. CHNS elemental analysis results of the samples
[0067] Table 5 shows that the carbon mass fraction of the four samples ranged from 27.830% to 29.900%, indicating a high proportion of carbon in the products. Nitrogen was still detected at 0.881 wt% in the GC-0 sample, indicating that a small amount of nitrogen was retained in the heat-treated product without the addition of iron salts. With increasing Fe molar percentage, the overall nitrogen content of the sample increased from 0.881 wt% to 6.552 wt%, a change consistent with the formation of nitrogen-containing crystalline phases and the increase in overall nitrogen retention in the material.
[0068] The above elemental analysis results are used to describe the overall elemental composition of the material and are not used to distinguish between lattice nitrogen in Fe3Mo3N and nitrogen species in the carbon matrix, nor are they used to calculate the quantitative phase content of Fe3Mo3N. Since the CHNS elemental analysis did not determine elements such as Fe, Mo, and O, the sum of the mass fractions of C, N, H, and S in the table is not equal to 100%.
[0069] 6. SEM and TEM microstructure characterization Scanning electron microscopy was performed on the GC-25 sample obtained in Example 1 (results are shown below). Figure 5 (as shown) and transmission electron microscopy observations (results as shown) Figure 6 (As shown). The electron beam accelerating voltage for SEM testing was 10.00 kV, the working distance was 7.5 mm, and an InLens signal was used. Figure 5 (A) and Figure 5 (B) Surface morphology at magnifications of 40,000 and 20,000, respectively.
[0070] like Figure 5 As shown, the GC-25 sample consists of irregular clusters formed by the stacking of nanoscale particles. The surface of the clusters is relatively rough, and there are gaps and pores of different sizes between particles and between clusters. Filamentous interconnections can be observed locally. This hierarchical morphology increases the contact interface between particles and forms a more tortuous propagation path, which can provide a structural basis for electromagnetic wave scattering and interface polarization.
[0071] like Figure 6 (A) ~ Figure 6 As shown in (C), nanoparticles with a deeper contrast are dispersed in carbon-based components with a shallower contrast, and local particles are adjacent to each other and form composite clusters. Figure 6(D) Two sets of lattice fringes can be distinguished in adjacent regions of the same field of view. The lattice fringes with an interplanar spacing of approximately 0.277 nm belong to the {400} crystal plane family of Fe3Mo3N, while the lattice fringes with an interplanar spacing of approximately 0.224 nm belong to the {101} crystal plane family of Mo2C. These results indicate that Fe3Mo3N and Mo2C coexist at the nanoscale and form close contacts in local regions.
[0072] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.
[0073] Although preferred embodiments of the present application have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are limited to all changes and modifications that include the preferred embodiments and fall within the scope of the embodiments of the present application.
[0074] Finally, it should be noted that in this application, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or terminal device that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or terminal device. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or terminal device that includes said element.
[0075] This application uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material, characterized in that, The composite electromagnetic shielding material includes a carbon matrix and Fe3Mo3N and Mo2C crystal phases dispersed in the carbon matrix, wherein the Fe3Mo3N and Mo2C crystal phases are in contact with each other at the nanoscale to form a heterogeneous interface.
2. The Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material according to claim 1, characterized in that, The composite electromagnetic shielding material contains 27% to 30% carbon and 3.0% to 5.5% nitrogen by mass.
3. The Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material according to claim 1, characterized in that, The composite electromagnetic shielding material has a high-field magnetization of 5 emu·g under a magnetic field of 298K and 10kOe. -1 ~20emu·g -1 Its coercivity is 80 Oe to 200 Oe.
4. A method for preparing the Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material according to any one of claims 1 to 3, characterized in that, Includes the following steps: Iron salt, molybdenum salt and melamine were used as precursors. They were ground and mixed evenly with the aid of ethanol, and then dried to obtain powdered precursors. The powdered precursor was heated to 680℃~720℃ in a nitrogen atmosphere and held at that temperature. After cooling, the Fe3Mo3N / Mo2C biphase carbon-based composite electromagnetic shielding material was obtained.
5. The preparation method according to claim 4, characterized in that, The iron salt is a soluble divalent iron salt or a soluble trivalent iron salt, including at least one of ferrous sulfate heptahydrate, ferric chloride hexahydrate, and ferric nitrate nonahydrate; the molybdenum salt is a molybdenum-containing ammonium salt, including ammonium molybdate or ammonium heptamolybdate tetrahydrate; the molar ratio of the molybdenum salt to the melamine is 1:
20.
6. The preparation method according to claim 5, characterized in that, In the precursor, the amount of iron accounts for 25% to 50% of the total amount of iron and molybdenum.
7. The preparation method according to claim 6, characterized in that, In the precursor, the amount of iron accounts for 25% of the total amount of iron and molybdenum, and the molar ratio of ferric nitrate nonahydrate, ammonium heptamolybdate tetrahydrate, and melamine is 7 / 3:1:
20.
8. The preparation method according to claim 4, characterized in that, The step of heating the powdered precursor to 680°C~720°C under a nitrogen atmosphere and holding it at that temperature includes: Before heating, purge with nitrogen gas at a flow rate of 450 sccm to 550 sccm for 8 to 12 minutes. Adjust the nitrogen flow rate to 95 sccm~105 sccm, and raise the temperature to 680℃~720℃ at a rate of 3℃ / min~7℃ / min, and hold for 100min~150min.
9. The preparation method according to claim 4, characterized in that, The cooling method includes continuously introducing nitrogen gas and cooling the furnace to room temperature.
10. The application of the Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material according to any one of claims 1 to 3, characterized in that, The Fe3Mo3N / Mo2C dual-phase carbon-based composite electromagnetic shielding material is used as a functional filler to prepare electromagnetic interference shielding components or electromagnetic wave attenuation components.
